Fuel coal water slurry and preparation method thereof

By introducing carbon-based nanogenic modifiers in the coal plasma, the interface tension of coal-solution is adjusted, the problem of high water volatilization temperature and low thermal value during the combustion process of the coal plasma slurry is solved, and the high-level and energy-saving is low. Coal improvement has improved the thermal value and stability of the coal slurry.

CN119351147APending Publication Date: 2025-01-24CHINA SHENHUA ENERGY CO LTD HARWUSU OPEN-PIT COAL MINE +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411470904.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing water coal slurry has high water volatilization temperature and low calorific value during combustion, which limits the industrial application value of low-order coal.

Method used

The fuel water coal plasma containing the coal powder, water, additives and carbon -based nanogenic modifiers. The carbon -based nanogenic modified agent has a tubular structure or laminar structure. By adjusting the interface tension of the coal-solution, reducing the internal water content in the pore structure of the coal granularity.

Benefits of technology

The volatilization temperature of the water during the combustion process is reduced, the thermal value of the fuel water coal plasma is increased, the decentralization and stability of the coal is enhanced, the low -order coal improvement process is simplified and the quality of the quality is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351147A_ABST
    Figure CN119351147A_ABST
Patent Text Reader

Abstract

The invention provides fuel coal water slurry and a preparation method thereof. The fuel coal water slurry comprises pulverized coal, water, an additive and a carbon-based nano material modifier, the additive comprises a dispersant and a stabilizer, the carbon-based nano material modifier has a tubular structure or a layered structure, and the average pipe diameter or interlayer spacing of the carbon-based nano material modifier is smaller than the average pore diameter of the pulverized coal. Compared with fuel coal water slurry not containing the carbon-based nano material modifier, the coal water slurry can reduce the combustion temperature, inhibit mineral substance pyrolysis and generation of nitrogen oxides and carbon monoxide, thereby reducing the heat loss of coal combustion. The carbon-based nano-material modifier has a tubular structure or a layered structure, and compared with other ranges, the average pipe diameter or interlayer spacing of the carbon-based nano-material modifier is limited to be smaller than the average pore diameter of the pulverized coal, so that water can leave a coal particle pore structure and enter the carbon-based nano-material modifier, the volatilization temperature of the water in the combustion process is reduced, and the combustion efficiency is improved. Therefore, the calorific value of the fuel coal water slurry is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of coal chemical industry, and in particular to a fuel water-coal slurry and a preparation method thereof. Background Art

[0002] Coal-water slurry is a coal-based fluid fuel with high combustion efficiency, convenient transportation, environmental protection and energy saving. It is considered to be an alternative fuel to natural gas and oil and has broad application prospects. With the excessive mining and use of high-rank coal, the supply of high-rank coal is becoming increasingly tight. On the contrary, low-rank coal reserves are huge, accounting for about 50% of the world's total coal resources. However, due to its high ash content and high water content, low heating efficiency and high transportation cost, low-rank coal has limited its industrial application value. Therefore, improving the quality of low-rank coal and preparing it into coal-water slurry is one of the hot research topics in the clean utilization of coal.

[0003] Most existing studies focus on reducing the internal water content in the pore structure of coal particles and reducing the number of hydrophilic groups on the surface of coal particles. The methods involved mainly include heating modification dehydration, microwave radiation dehydration, hydrothermal modification dehydration, additive blocking of capillary channels, and flotation removal of hydrophilic ash. These methods can remove the internal water contained in the mesopores of coal particles and digest the hydrophilic components of coal particles to a certain extent, but these methods increase the energy consumption and process complexity of coal powder pretreatment, and do not destroy the pore structure of coal particles. Due to the capillary effect, H2O will be re-adsorbed into the capillary channels of coal during the preparation of water-coal slurry, causing the viscosity of the water-coal slurry to increase rapidly, lose fluidity, and increase the resistance to grinding and pulping.

[0004] In addition, the micro-nanostructure pores of coal particles have a "water locking effect", which causes the volatilization temperature (peak value) of H2O in the capillary channels of coal particles to be mostly higher than 100°C during combustion, resulting in the calorific value of water-coal slurry combustion being lower than the calorific value of the same amount of coal powder. Taking lignite as an example, the volatilization temperature (peak value) of its H2O during combustion can be as high as 117°C, which is much higher than the volatilization temperature of ordinary H2O at room temperature and pressure of 100°C, causing the calorific value of burning lignite water-coal slurry to be much lower than the calorific value of the same amount of dried coal powder.

[0005] Considering the extensive demand for clean utilization of coal and water-coal slurry in power generation and coal chemical industry, exploring new methods for improving the quality of low-rank coal and making pulp with high efficiency and energy saving has multiple meanings in terms of application, environmental protection and economy in the field of water-coal slurry technology. The current water-coal slurry has a high water volatilization temperature and low calorific value during combustion due to the "water locking effect" of the pores in the coal particle structure.

[0006] In summary, it is of great significance to study and develop a fuel water-coal slurry with low water volatilization temperature and high calorific value during combustion and a preparation method thereof. Summary of the invention

[0007] The main purpose of the present invention is to provide a fuel water-coal slurry and a preparation method thereof, so as to solve the problems of high water volatilization temperature and low calorific value of water-coal slurry during combustion in the prior art.

[0008] In order to achieve the above-mentioned purpose, the present invention provides a fuel water-coal slurry on the one hand, which includes coal powder, water, additives and carbon-based nanomaterial modifiers, wherein the additives include dispersants and stabilizers, and the carbon-based nanomaterial modifier has a tubular structure or a layered structure, and the average tube diameter or interlayer spacing of the carbon-based nanomaterial modifier is smaller than the average pore diameter of the coal powder.

[0009] Furthermore, the coal powder is modified coal powder obtained after cavitation treatment.

[0010] Furthermore, the content of the carbon-based nanomaterial modifier is 0.5-5.0wt% based on the weight percentage of the coal powder.

[0011] Furthermore, the fuel water-coal slurry includes, by weight, 35 to 70 parts of coal powder, 28.5 to 64.5 parts of a first mixture of an additive and water, and 0.5 to 1.5 parts of a carbon-based nanomaterial modifier.

[0012] Furthermore, the absolute value of the difference between the average tube diameter or interlayer spacing of the carbon-based nanomaterial modifier and the average pore diameter of the coal powder is 1 to 50 nm.

[0013] Furthermore, the average tube diameter or interlayer distance of the carbon-based nanomaterial modifier is 1 to 100 nm.

[0014] Furthermore, the average pore size of the coal powder is 2 to 100 nm.

[0015] Furthermore, the carbon-based nanomaterial modifier is selected from one or more of the group consisting of single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, graphene oxide and their transition metal modified derivatives.

[0016] Furthermore, the transition metal element in the transition metal modified derivative is selected from one or more of the group consisting of Fe, Ti, Ni, Co and Mn.

[0017] Furthermore, the sum of the weight of the dispersant and the stabilizer accounts for 0.1-2 wt % of the weight of the coal powder.

[0018] Further, the dispersant is selected from one or more of the group consisting of lignin sulfonate, polynaphthalene sulfonate and humate.

[0019] Furthermore, the stabilizer is selected from one or more of the group consisting of carboxymethyl cellulose, polyacrylamide, emulsified alkyl ketene dimer, vegetable gum, sodium stearate and sodium hexametaphosphate.

[0020] Furthermore, the weight ratio of the dispersant to the stabilizer is (1-10):(0.05-5).

[0021] Furthermore, the particle size D50 of the fuel water-coal slurry is ≤15 μm.

[0022] Furthermore, the coal powder is selected from one or more of the group consisting of bituminous coal powder, sub-bituminous coal powder, lignite powder and blended coal powder including gangue and biochar.

[0023] Furthermore, in 100s -1 At the shear rate, the apparent viscosity of the fuel water-coal slurry is ≤1200mPa·s.

[0024] In order to achieve the above-mentioned purpose, another aspect of the present invention provides a method for preparing the above-mentioned fuel water-coal slurry provided in the present application, and the method for preparing the fuel water-coal slurry comprises: step S1, crushing the raw coal to obtain coal powder; step S2, grinding the second mixture of coal powder, additives and water to obtain a ground product; step S3, mixing the ground product with a carbon-based nanomaterial modifier and optionally performing cavitation treatment to obtain a fuel water-coal slurry.

[0025] Furthermore, the content of the coal powder is 35-65wt% based on the weight percentage of the second mixture.

[0026] Furthermore, the particle size D50 of the solid particles in the grinding product is ≤120 μm.

[0027] Furthermore, step S3 comprises: mixing the ground product with a carbon-based nanomaterial modifier and optionally performing cavitation treatment, and successively filtering, shearing and aging to obtain a fuel water-coal slurry.

[0028] Furthermore, a cavitation reactor is used to perform cavitation treatment.

[0029] Furthermore, the cavitation reactor is selected from a hydrodynamic cavitation reactor, an ultrasonic cavitation reactor, an arc micro-explosion reactor, a microwave reactor or a ball milling reactor.

[0030] Furthermore, the inlet pressure of the cavitation reactor is 0.1-10 MPa, and the single cavitation treatment time is 3-30 min.

[0031] Furthermore, the particle size D50 of the coal powder in step S1 is ≤ 50 mesh.

[0032] By applying the technical solution of the present invention, the coal powder in this application is derived from medium and low-rank coal with abundant reserves, and can be efficiently utilized as a combustible component in the fuel water-coal slurry. The introduction of water makes the water-coal slurry have fluidity similar to oil, and it can be transported by pipeline, pumped and stored in a closed manner for a long time like oil, so that the water-coal slurry can be more convenient and economical in storage and transportation. Additives include dispersants and stabilizers. The introduction of dispersants can inhibit the mutual attraction and aggregation between coal powder particles, and can make the coal powder more evenly dispersed in water to form a stable suspension; the introduction of stabilizers can inhibit the coagulation and sedimentation of coal powder in water-coal slurry, thereby improving the long-term stability of the fuel water-coal slurry. The introduction of carbon-based nanomaterial modifiers can adjust the interfacial tension of coal-solution, thereby reducing the internal water content in the pore structure of coal particles.

[0033] Compared with fuel water-coal slurry that does not contain carbon-based nanomaterial modifiers, it can lower the combustion temperature, inhibit mineral pyrolysis and the generation of nitrogen oxides and carbon monoxide, thereby reducing the heat loss of coal combustion.

[0034] The carbon-based nanomaterial modifier has a tubular structure or a layered structure. Compared with other ranges, limiting the average tube diameter or interlayer spacing of the carbon-based nanomaterial modifier to be smaller than the average pore diameter of coal powder is beneficial for water to leave the pore structure of coal particles and enter the carbon-based nanomaterial modifier, which is beneficial to reducing the volatilization temperature of water during combustion, thereby facilitating improving the calorific value of the fuel water-coal slurry. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0036] Figure 1 The flow chart of preparing fuel water-coal slurry of the present invention is shown;

[0037] Figure 2 The TG-DSC analysis results of the additive-enhanced ultrafine fuel water-coal slurry (Zhunneng-5500 coal (provided by Harwusu open-pit coal mine)) of Example 1 are shown;

[0038] Figure 3 The particle size distribution of the additive-enhanced ultrafine fuel water-coal slurry (Zhunneng-5500 coal (provided by Harwusu open-pit coal mine)) of Example 1 is shown;

[0039] Figure 4 The apparent viscosity of the additive-enhanced ultrafine fuel water-coal slurry (Zhunneng-5500 coal (provided by Harwusu open-pit coal mine)) of Example 1 is shown;

[0040] Figure 5The TG-DSC analysis results of the additive-enhanced ultrafine fuel water-coal slurry (lignite (provided by Harwusu open-pit coal mine)) of Example 5 are shown;

[0041] Figure 6 The TG-DSC analysis results of the crude water-coal slurry (Zhunneng-5500 coal (provided by Harwusu open-pit coal mine)) of Comparative Example 1 are shown;

[0042] Figure 7 The TG-DSC analysis results of the ultrafine water-coal slurry (lignite (provided by Harwusu open-pit coal mine)) of Comparative Example 2 are shown. DETAILED DESCRIPTION

[0043] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0044] As described in the background art, the existing water-coal slurry has the problems of high water volatilization temperature and low calorific value during the combustion process. In order to solve the above technical problems, the first aspect of the present application provides a fuel water-coal slurry, which comprises coal powder, water, additives and carbon-based nanomaterial modifiers, wherein the additives include dispersants and stabilizers, the carbon-based nanomaterial modifiers have a tubular structure or a layered structure, and the average tube diameter or interlayer spacing of the carbon-based nanomaterial modifier is smaller than the average pore diameter of the coal powder.

[0045] In the present application, the coal powder is derived from medium and low-rank coal with abundant reserves, and can be efficiently utilized as a combustible component in the fuel water-coal slurry. The introduction of water makes the water-coal slurry have fluidity similar to oil, and it can be transported by pipeline, pumped and stored in a closed manner for a long time like oil, so that the water-coal slurry can be more convenient and economical in storage and transportation. Additives include dispersants and stabilizers. The introduction of dispersants can inhibit the mutual attraction and aggregation between coal powder particles, and can make the coal powder more evenly dispersed in water to form a stable suspension; the introduction of stabilizers can inhibit the coagulation and sedimentation of coal powder in water-coal slurry, thereby improving the long-term stability of the fuel water-coal slurry. The introduction of carbon-based nanomaterial modifiers can adjust the interfacial tension of coal-solution, thereby reducing the internal water content in the pore structure of coal particles. The fuel water-coal slurry of the present invention has good fluidity and high reaction activity.

[0046] Compared with fuel water-coal slurry that does not contain carbon-based nanomaterial modifiers, it can lower the combustion temperature, inhibit mineral pyrolysis and the generation of nitrogen oxides and carbon monoxide, thereby reducing the heat loss of coal combustion.

[0047] The carbon-based nanomaterial modifier has a tubular structure or a layered structure. Compared with other ranges, limiting the average tube diameter or interlayer spacing of the carbon-based nanomaterial modifier to be smaller than the average pore diameter of coal powder is beneficial for water to leave the pore structure of coal particles and enter the carbon-based nanomaterial modifier, which is beneficial to reducing the volatilization temperature of water during combustion, thereby facilitating improving the calorific value of the fuel water-coal slurry.

[0048] In a preferred embodiment, the coal powder is a modified coal powder obtained after cavitation treatment. The modified coal powder obtained after cavitation treatment can have an ultrafine particle size and a higher surface energy, thereby increasing the combustion rate of the water-coal slurry, and the rate of the coal combustion reaction reaches 2 to 3 times that when the carbon-based nanomaterial modifier is not used, and the heat released by combustion per unit time is significantly increased.

[0049] In a preferred embodiment, the content of the carbon-based nano material modifier is 0.5-5.0wt% in terms of the weight percentage of the coal powder. The content of the carbon-based nano material modifier includes but is not limited to the above range, and limiting it within the above range is beneficial to reducing the volatilization temperature of water during combustion, thereby facilitating the improvement of the calorific value of the fuel water-coal slurry. For example, the content of the carbon-based nano material modifier can be 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.25, 1.3, 1.4 or 1.5wt%.

[0050] In order to further reduce the volatilization temperature of water during the combustion process, thereby further improving the calorific value, in a preferred embodiment, the fuel water-coal slurry includes, by weight, 35 to 70 parts of coal powder, 28.5 to 64.5 parts of a first mixture of additives and water, and 0.5 to 1.5 parts of a carbon-based nanomaterial modifier.

[0051] In order to further reduce the internal water content in the pore structure of coal particles, lower the volatilization temperature of water during combustion, and thus further increase the combustion calorific value, in a preferred embodiment, the absolute value of the difference between the average tube diameter or interlayer spacing of the carbon-based nanomaterial modifier and the average pore diameter of the coal powder is 1 to 50 nm.

[0052] In a preferred embodiment, the average tube diameter or interlayer spacing of the carbon-based nanomaterial modifier is 1 to 100 nm. The average tube diameter or interlayer spacing of the carbon-based nanomaterial modifier includes but is not limited to the above range, and limiting it within the above range is conducive to reducing the internal water content in the pore structure of coal particles, reducing the volatilization temperature of water during combustion, and reducing the energy consumed by water evaporation during the combustion of water-coal slurry, thereby facilitating the improvement of combustion calorific value.

[0053] In a preferred embodiment, the average pore size of the coal powder is 2-100 nm. The average pore size of the coal powder pores includes but is not limited to the above range, which is conducive to reducing the internal water content in the pore structure of the coal particles, thereby facilitating the improvement of the combustion calorific value.

[0054] In a preferred embodiment, the carbon-based nanomaterial modifier includes, but is not limited to, one or more of the group consisting of single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, graphene oxide, and their transition metal modified derivatives. Compared with other types, the above-mentioned types of carbon-based nanomaterial modifiers are widely available and low in cost.

[0055] The present application has no particular restrictions on the types of transition metals in the transition metal modified derivatives, and commonly used types in the art can be used. In a preferred embodiment, the transition metal in the transition metal modified derivatives includes but is not limited to one or more of the group consisting of Fe, Ti, Ni, Co and Mn.

[0056] In a preferred embodiment, the sum of the weight of the dispersant and the stabilizer accounts for 0.1-2 wt % of the weight of the coal powder. The sum of the weight of the dispersant and the stabilizer includes but is not limited to the above range, which is beneficial to improving the stability of the fuel water-coal slurry.

[0057] The present application has no particular limitation on the type of dispersant, and commonly used types in the art may be used. In a preferred embodiment, the dispersant includes, but is not limited to, one or more of the group consisting of lignin sulfonate, polynaphthalene sulfonate, and humate.

[0058] In a preferred embodiment, the stabilizer includes, but is not limited to, one or more of the group consisting of carboxymethyl cellulose, polyacrylamide, emulsified alkyl ketene dimer, vegetable gum, sodium stearate and sodium hexametaphosphate. The above stabilizers are widely available and low in cost.

[0059] In order to further improve the stability of the fuel water-coal slurry, the weight ratio of the dispersant to the stabilizer is (1-10):(0.05-5).

[0060] In a preferred embodiment, the particle size D50 of the fuel water-coal slurry is ≤15 μm. The range of the particle size D50 of the fuel water-coal slurry includes but is not limited to the above range, and limiting it to the above range is conducive to improving combustion efficiency.

[0061] In this article, "D50" refers to the particle size corresponding to the cumulative particle size distribution percentage of the sample reaching 50%. In physical terms, this means that 50% of the particles have a particle size greater than D50, and 50% of the particles have a particle size less than D50. There are many ways to measure D50, such as laser diffraction. The "D10" and "D90" that appear below correspond to the 10% and 90% particle sizes, respectively.

[0062] In a preferred embodiment, the coal powder includes but is not limited to one or more of the group consisting of bituminous coal powder, sub-bituminous coal powder, lignite powder and coal powder blended with gangue and biochar. Compared with other types, the above types of coal powder are widely available and low in cost.

[0063] In order to improve the pumping performance, combustion efficiency and storage stability of fuel water-coal slurry, -1 At the shear rate, the apparent viscosity of the fuel water-coal slurry is ≤1200mPa·s.

[0064] The second aspect of the present application also provides a method for preparing the above-mentioned fuel water-coal slurry provided by the present application, and the preparation method of the fuel water-coal slurry includes: step S1, crushing the raw coal to obtain coal powder; step S2, grinding the second mixture of coal powder, additives and water to obtain a ground product; step S3, mixing the ground product with a carbon-based nanomaterial modifier and optionally performing cavitation treatment to obtain a fuel water-coal slurry.

[0065] Crushing the raw coal to obtain coal powder can improve the dispersibility of the coal powder in subsequent processes; grinding the second mixture of coal powder, additives and water to obtain a ground product can improve the dispersion stability of the coal powder and prevent the coal powder from agglomerating and settling, thereby making the water-coal slurry smoother during transportation and reducing the risk of blockage. It is suitable for long-distance pipeline transportation and reduces transportation and maintenance costs; mixing the ground product with a carbon-based nanomaterial modifier can cause the internal water (concave water, inert water) in the pore structure of the coal particles, which is caused by the average tube diameter or interlayer spacing of the carbon-based nanomaterial modifier being smaller than the average pore diameter of the coal powder, to leave and enter the carbon-based nanomaterial modifier to become convex water (active water), which can regulate the pore size of the water-coal slurry. The internal water content of the pore structure is conducive to reducing the volatilization temperature of water during combustion, thereby helping to increase the calorific value of the fuel water-coal slurry. In addition, the carbon-based nanomaterial modifier also acts as a catalyst, which can increase the combustion rate; cavitation treatment can be optionally performed. The bubbles generated by cavitation will form local high temperature and high pressure when they collapse, which can break large particles of coal powder into fine particles, destroy the pore structure of coal particles, and help the coal powder to be crushed into ultrafine particles. In addition, cavitation treatment can cause water to produce hydrogen radicals (·H) and hydroxyl radicals (·OH), among which hydroxyl radicals (·OH) are very active and help to convert aliphatic carbon-hydrogen bonds in coal powder into aromatic carbon-hydrogen bonds, which can release more heat during combustion. By combining the destruction of the pore structure of low-rank coal with the regulation of the water content in coal particles in the same process, the quality improvement process of low-rank coal is simplified and the energy consumption of quality improvement is reduced.

[0066] In order to improve the slurrying properties, in a preferred embodiment, the content of the coal powder is 35-65wt% based on the weight percentage of the second mixture.

[0067] In a preferred embodiment, the particle size D50 of the solid particles in the ground product is ≤120 μm. The particle size D50 of the solid particles in the ground product includes but is not limited to the above range, and limiting it to the above range is conducive to improving the processing efficiency in subsequent processes.

[0068] In a preferred embodiment, step S3 comprises: mixing the ground product with a carbon-based nanomaterial modifier and optionally performing cavitation treatment, filtering, shearing and maturing in sequence to obtain a fuel water-coal slurry. Filtration can remove large particle impurities and insoluble matter in the water-coal slurry, thereby reducing wear on pumps and pipelines and improving system reliability; shearing can destroy the flocculation structure in the water-coal slurry, reduce its viscosity, and make it easier to flow and pump; maturation can improve the combustion characteristics of the water-coal slurry, making it more complete and uniform during combustion, and improving combustion efficiency.

[0069] In order to facilitate the cavitation treatment, in one embodiment, a cavitation reactor is used to perform the cavitation treatment.

[0070] The present application does not particularly limit the type of cavitation reactor, and commonly used types in the art can be used. In a preferred embodiment, the cavitation reactor includes but is not limited to a hydrodynamic cavitation reactor, an ultrasonic cavitation reactor, an arc micro-explosion reactor, a microwave reactor or a ball milling reactor. Preferably, the ball milling reactor is a high-speed ball milling reactor.

[0071] In order to improve the cavitation efficiency, in a preferred embodiment, the inlet pressure of the cavitation reactor is 0.1-10 MPa, and the single cavitation treatment time is 3-30 min. Whether to perform repeated cavitation treatment is determined according to actual production conditions.

[0072] In a preferred embodiment, the particle size D50 of the coal powder in step S1 is ≤ 50 mesh. The range of the particle size D50 of the coal powder in step S1 includes but is not limited to the above range, and limiting it to the above range is conducive to improving the dispersibility of the coal powder in subsequent processes and facilitating the efficient use of the coal powder.

[0073] The present application is further described in detail below in conjunction with specific embodiments. These embodiments are intended to better further understand the present invention, are not limited to the best implementation mode, and do not limit the content and protection scope of the present invention. Any product that is the same or similar to the present invention and is obtained by anyone under the inspiration of the present invention or by combining the present invention with the features of other prior arts shall fall within the protection scope of the present invention.

[0074] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The experimental methods used in the following embodiments are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following embodiments, unless otherwise specified, can all be obtained from commercial sources.

[0075] Example 1

[0076] like Figure 1 As shown in the preparation flow chart, a method for preparing a fuel water-coal slurry comprises:

[0077] (1) The junneng-5500 coal with a high ash content (provided by the Harwusu open-pit coal mine) was crushed to a particle size D50≤50 mesh by a crusher to obtain coal powder;

[0078] (2) 0.94 g of an additive and 185.56 g of water are mixed to obtain a first mixture, and 312.5 g of coal powder and a second mixture of the first mixture are wet-ground using a ball mill to obtain a ground product having a D50 of 56 μm; wherein the additive comprises sodium lignin sulfonate and polyacrylamide in a weight ratio of 1:0.05, and the content of the coal powder is 62.5 wt % based on the weight percentage of the second mixture; and the weight percentage of the additive to the coal powder is 0.3 wt %;

[0079] (3) mixing the ground product obtained in step (2) with multi-walled carbon nanotubes in a hydrodynamic cavitation reaction tank, wherein the amount of the multi-walled carbon nanotubes is 1.5 wt % based on the weight percentage of the coal powder, wherein the average tube diameter of the multi-walled carbon nanotubes is 35 nm, and the average pore diameter of the pores of the coal powder is 40 nm, and the ground product and the multi-walled carbon nanotubes are uniformly mixed in the hydrodynamic cavitation reaction tank at 7000 rpm; and then cavitation treatment is performed at 23000 rpm to obtain a cavitation product with a D50 of 2.62 μm;

[0080] (4) filtering to remove impurities in the cavitation product obtained in step (3), and then subjecting the product to stirring, high shearing and homogenizing dry treatment to obtain a fuel water-coal slurry.

[0081] The weight percentage of coal powder in the fuel water-coal slurry prepared in this embodiment is 62.21wt%, and D50 is 2.62μm; the fuel water-coal slurry has good fluidity and rheological properties, and its shear rate is 100s at a temperature of 30°C. -1 The viscosity is 765mPa·s; the stability test results show that there is no stratification, free water precipitation, and hard precipitation for more than 30 days, which meets the quality requirements of the national standard GB / T 18855-2014 fuel coal slurry.

[0082] Figure 2 The TG-DSC analysis results of the fuel water-coal slurry of this embodiment are shown, wherein the volatilization peak temperature T1 is 69.8°C, the reaction mass decrease rate is -35.03% / min, and the cartridge calorific value Q is 6536.5 kcal / kg (coal powder).

[0083] Figure 3 The particle size distribution of the fuel water-coal slurry of this embodiment is shown, where D10 = 0.248 μm, D50 = 1.104 μm, and D90 = 5.439 μm.

[0084] Figure 4 The apparent viscosity of the fuel water-coal slurry of this embodiment is shown, which is measured by the rheometer software (Anton Paar RheoCmpass) of Anton Paar.

[0085] Example 2

[0086] The difference from Example 1 is that the amount of coal powder in step (2) is changed so that the weight percentage of coal powder in the fuel water-coal slurry is reduced to 38.85wt%; the content of multi-walled carbon nanotubes is 1wt% based on the weight percentage of coal powder.

[0087] Example 3

[0088] The difference from Example 1 is that the raw material is Junneng 4000 coal powder (provided by Har Usu open-pit coal mine); the amount of coal powder in step (2) is changed so that the weight percentage of coal powder in the fuel water-coal slurry is 51.00wt%; and the content of multi-walled carbon nanotubes is 1.25wt% based on the weight percentage of coal powder.

[0089] Example 4

[0090] The difference from Example 1 is that the raw material is Xinjiang 7600 coal powder (provided by Har Usu open-pit coal mine); the amount of coal powder in step (2) is changed so that the weight percentage of coal powder in the fuel water-coal slurry is 48.80wt%; and the content of multi-walled carbon nanotubes is 1.25wt% based on the weight percentage of coal powder.

[0091] Example 5

[0092] The difference from Example 1 is that the raw material is Shuangyashan lignite powder (provided by Har Usu open-pit coal mine); the amount of coal powder in step (2) is changed so that the weight percentage of coal powder in the fuel water-coal slurry is 46.50wt%; and the content of multi-walled carbon nanotubes is 1.5wt% based on the weight percentage of coal powder.

[0093] Figure 5 The TG-DSC analysis results of the fuel water-coal slurry of this embodiment are shown, wherein the volatilization peak temperature T1 is 102.0°C, the reaction mass decrease rate is -41.14% / min, and the cartridge calorific value Q is 5658.2 kcal / kg (coal powder).

[0094] Example 6

[0095] The difference from Example 1 is that in step (3), the content of multi-walled carbon nanotubes is 0.5 wt % based on the weight percentage of the coal powder.

[0096] Example 7

[0097] The difference from Example 1 is that in step (3), the content of multi-walled carbon nanotubes is 5.5 wt % based on the weight percentage of the coal powder.

[0098] Comparative Example 1

[0099] The difference from Example 1 is that step (3) is omitted, that is, no cavitation treatment is performed and no multi-walled carbon nanotubes are added.

[0100] Figure 6 The TG-DSC analysis results of the crude water-coal slurry of this comparative example are shown, wherein the volatilization peak temperature T1 is 107.18°C, the reaction mass decrease rate is -3.97% / min, and the bomb calorific value Q is 5038.8 kcal / kg (coal powder).

[0101] Comparative Example 2

[0102] The difference from Example 5 is that no multi-walled carbon nanotubes are added.

[0103] Figure 7 The TG-DSC analysis results of the ultrafine water-coal slurry of this comparative example are shown, wherein the volatilization peak temperature T1 is 117.4°C, the reaction mass decrease rate is -13.66% / min, and the bomb calorific value Q is 4354.64 kcal / kg (coal powder).

[0104] Comparative Example 3

[0105] The difference from Example 1 is that no multi-walled carbon nanotubes are added.

[0106] The results of the volatilization peak temperature T1 (°C), the reaction mass reduction rate (% / min) and the cartridge calorific value Q (kcal / kg (coal powder)) (standard GB / T213-2008) in the embodiments and comparative examples are shown in Table 1.

[0107] The D50 of Examples 1-7 and Comparative Examples 1-3 was measured using a laser particle size analyzer.

[0108] In PerkinElmer thermal analysis, TG-DSC (oxygen atmosphere) was used to test the volatilization peak temperature T1 (° C.), reaction peak temperature T2 (° C.) and reaction mass decrease rate (% / min) of Examples 1-7 and Comparative Examples 1-3.

[0109] The oxygen bomb calorimeter was used to test the bomb calorific value Q (kcal / kg (coal powder)) of Examples 1 to 7 and Comparative Examples 1 to 3.

[0110] Table 1

[0111]

[0112]

[0113] From the above description, it can be seen that the above-mentioned embodiments of the present invention achieve the following technical effects: the coal powder in this application is derived from medium and low-rank coal with abundant reserves, and can be efficiently utilized as a combustible component in the fuel water-coal slurry. The introduction of water makes the water-coal slurry have fluidity similar to oil, and it can be transported by pipeline, pumped and stored in a closed manner for a long time like oil, so that the water-coal slurry can be more convenient and economical in storage and transportation. Additives include dispersants and stabilizers. The introduction of dispersants can inhibit the mutual attraction and aggregation between coal powder particles, and can make the coal powder more evenly dispersed in water to form a stable suspension; the introduction of stabilizers can inhibit the coagulation and sedimentation of coal powder in water-coal slurry, thereby improving the long-term stability of the fuel water-coal slurry. The introduction of carbon-based nanomaterial modifiers can adjust the interfacial tension of coal-solution, thereby reducing the internal water content in the pore structure of coal particles.

[0114] Compared with fuel water-coal slurry that does not contain carbon-based nanomaterial modifiers, it can lower the combustion temperature, inhibit mineral pyrolysis and the generation of nitrogen oxides and carbon monoxide, thereby reducing the heat loss of coal combustion.

[0115] The carbon-based nanomaterial modifier has a tubular structure or a layered structure. Compared with other ranges, the average tube diameter or interlayer spacing of the carbon-based nanomaterial modifier is limited to be smaller than the average pore diameter of the coal powder, which is beneficial for water to leave the pore structure of the coal particles and enter the carbon-based nanomaterial modifier, which is beneficial for reducing the volatilization temperature of water during the combustion process, thereby helping to increase the calorific value of the fuel water-coal slurry.

[0116] Compared with the crude water-coal slurry of comparative example 1, the fuel water-coal slurry of Example 1 of the present invention has high reaction activity, the water evaporation temperature is reduced from 107.18°C of the crude water-coal slurry of comparative example 1 to 69.8°C, and the combustion rate (peak position) of the fuel water-coal slurry in oxygen is greatly improved: from -3.97% / min of the crude water-coal slurry of comparative example 1 to -35.03% / min.

[0117] Compared with the ultrafine water-coal slurry of comparative example 2, the fuel water-coal slurry of Example 5 of the present invention has high reaction activity, the water evaporation temperature is reduced from 117.4°C of the ultrafine water-coal slurry of comparative example 2 to 102.0°C, and the combustion rate (peak position) of the fuel water-coal slurry in oxygen is greatly improved: from -13.66% / min of the ultrafine water-coal slurry of comparative example 2 to -41.14% / min.

[0118] Compared with the ultrafine water-coal slurry of comparative example 3, the fuel water-coal slurry of Example 1 of the present invention has high reaction activity, the water evaporation temperature is reduced from 81.45°C of the ultrafine water-coal slurry of comparative example 3 to 69.8°C, and the combustion rate (peak position) of the fuel water-coal slurry in oxygen is greatly improved: from -8.76% / min of the ultrafine water-coal slurry of comparative example 3 to -35.03% / min.

[0119] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A fuel water-coal slurry, characterized in that: The fuel water-coal slurry includes coal powder, water, additives and carbon-based nanomaterial modifiers, wherein the additives include dispersants and stabilizers, the carbon-based nanomaterial modifiers have a tubular structure or a layered structure, and the average tube diameter or interlayer spacing of the carbon-based nanomaterial modifier is smaller than the average pore diameter of the coal powder.

2. The fuel water-coal slurry according to claim 1, characterized in that: The coal powder is modified coal powder obtained after cavitation treatment.

3. The fuel water-coal slurry according to claim 1 or 2, characterized in that: The content of the carbon-based nanomaterial modifier is 0.5-5.0wt% based on the weight percentage of the coal powder; Preferably, the fuel water-coal slurry comprises, by weight, 35 to 70 parts of the coal powder, 28.5 to 64.5 parts of the first mixture of the additive and water, and 0.5 to 1.5 parts of the carbon-based nanomaterial modifier.

4. The fuel water-coal slurry according to claim 1 or 2, characterized in that: The absolute value of the difference between the average tube diameter or interlayer spacing of the carbon-based nanomaterial modifier and the average pore diameter of the coal powder is 1 to 50 nm; Preferably, the average tube diameter or interlayer spacing of the carbon-based nanomaterial modifier is 1 to 100 nm; Preferably, the average pore size of the coal powder is 2 to 100 nm; Preferably, the carbon-based nanomaterial modifier is selected from one or more of the group consisting of single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, graphene oxide and their transition metal modified derivatives; Preferably, the transition metal element in the transition metal modified derivative is selected from one or more of the group consisting of Fe, Ti, Ni, Co and Mn.

5. The fuel water-coal slurry according to any one of claims 1 to 4, characterized in that: The sum of the weight of the dispersant and the stabilizer accounts for 0.1-2 wt% of the weight of the coal powder; Preferably, the dispersant is selected from one or more of the group consisting of lignin sulfonate, polynaphthalene sulfonate and humate; Preferably, the stabilizer is selected from one or more of the group consisting of carboxymethyl cellulose, polyacrylamide, emulsified alkyl ketene dimer, vegetable gum, sodium stearate and sodium hexametaphosphate; Preferably, the weight ratio of the dispersant to the stabilizer is (1-10):(0.05-5).

6. The fuel water-coal slurry according to any one of claims 1 to 5, characterized in that: The particle size of the fuel water-coal slurry D50≤15μm; Preferably, the coal powder is selected from one or more of the group consisting of bituminous coal powder, sub-bituminous coal powder, lignite powder and blended coal powder including gangue and biochar.

7. The fuel water-coal slurry according to any one of claims 1 to 5, characterized in that: In 100s -1 At the shear rate, the apparent viscosity of the fuel water-coal slurry is ≤1200 mPa·s.

8. A method for preparing a fuel water-coal slurry according to any one of claims 1 to 7, characterized in that: The preparation method of the fuel water-coal slurry comprises: Step S1, crushing raw coal to obtain coal powder; Step S2, grinding the second mixture of coal powder, additives and water to obtain a ground product; Step S3, mixing the ground product with a carbon-based nanomaterial modifier and optionally performing cavitation treatment to obtain the fuel water-coal slurry.

9. The method for preparing fuel water-coal slurry according to claim 8, characterized in that: The coal powder has a content of 35 to 65 wt % based on the weight percentage of the second mixture; Preferably, the particle size D50 of the solid particles in the grinding product is ≤120 μm; Preferably, the step S3 comprises: mixing the ground product with the carbon-based nanomaterial modifier and optionally performing the cavitation treatment, and sequentially filtering, shearing and aging to obtain the fuel water-coal slurry; Preferably, the cavitation treatment is performed using a cavitation reactor; Preferably, the cavitation reactor is selected from a hydrodynamic cavitation reactor, an ultrasonic cavitation reactor, an arc micro-explosion reactor, a microwave reactor or a ball milling reactor; Preferably, the inlet pressure of the cavitation reactor is 0.1-10 MPa, and the single cavitation treatment time is 3-30 min.

10. The method for preparing fuel water-coal slurry according to claim 8 or 9, characterized in that: The particle size D50 of the coal powder in step S1 is ≤ 50 mesh.

Citation Information

Cited By

  • Method for preparing high-concentration gasified coal water slurry from coal slime based on ultrasonic nanocrystallization

    CN121182531A